(untitled) (Revista de Ciências Agroveterinárias, 2024)
The objective of this work was to determine the importance of vigor during the initial establishment of the maize crop. The work was carried out using 8 lots of hybrid corn seed, in which four lots were characterized as high vigor and four lots characterized as low vigor. After obtaining the seeds, they were sown in the field to determine the association between vigor and seedling performance at 21 days after sowing. The experiment was carried out in a randomized block design with four replications. Seedling emergence was measured daily up to 21 days, and at the end of the period, the shoot length, root system length, total seedling length and their respective masses, root system volume and stem diameter were determined. Seed vigor was positively associated with all measured variables, except for root system length. All parameters evaluated were superior in the group of seeds characterized as having high vigor. It is concluded that the vigor of hybrid corn seeds is crucial for the higher speed and uniformity of emergence in the field, being essential to form seedlings with superior performance in field conditions.